School counseling services for gifted and talented students: a systematic review of literature - Lee, Zhi Jie; Hassan, Siti Aishah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Gifted and talented students are different from the other normal students and special attention is needed for due to their high cognitive ability and their socio-emotional conditions. Literatures show shortcomings and ineffectiveness of the counselling services to the gifted and talented students. The lack of effective interventions and approaches targeted to the students hinders the understanding on the importance of counseling services to the students. Hence, this study aims to explore the school counseling services for gifted and talented students. Based on inclusion and exclusion criteria, 10 articles were selected and reviewed. Findings from different journal sources conducted in different countries were assimilated to attain better understanding of the relevance of school counseling services to gifted and talented students. The role of the school counselors and the challenges in the school counseling services were also identified from the articles.